2013
DOI: 10.1177/0960327113475677
|View full text |Cite
|
Sign up to set email alerts
|

A 90-day subchronic toxicity study of neem oil, a Azadirachtaindica oil, in mice

Abstract: To determine the no-observed-adverse-effect level (NOAEL) of exposure and target organs of neem oil for establishing safety criteria for human exposure, the subchronic toxicity study with neem oil in mice was evaluated. The mice (10 per sex for each dose) was orally administered with neem oil with the doses of 0 (to serve as a control), 177, 533 and 1600 mg/kg/day for 90 days. After the treatment period, observation of reversibility or persistence of any toxic effects, mice were continuously fed without treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This is consistent with Khan et al that reported a significant increase in abnormal spermatozoa morphology in rats fed with neem leaf extract [12]. Wang et al concluded that the pathological damage on mice after administration of neem oil is reversible, which can be gradually restored after longterm discontinuation of the neem leaf extract [13].…”
Section: Advances In Biological Sciences Research Volume 12supporting
confidence: 90%
“…This is consistent with Khan et al that reported a significant increase in abnormal spermatozoa morphology in rats fed with neem leaf extract [12]. Wang et al concluded that the pathological damage on mice after administration of neem oil is reversible, which can be gradually restored after longterm discontinuation of the neem leaf extract [13].…”
Section: Advances In Biological Sciences Research Volume 12supporting
confidence: 90%
“…Katuura et al (2007) studied medicinal plants used for malaria in Mbarara municipality and Rwampara County from where 20 medicinal plants were reported, out of which 19 species were identified with their leaves or roots being used as decoctions or infusions (Table 1), either individually or in combination. Four of the plant species namely, M. indica, T. assiatica, V. amygdalina and V. lasiopus, commonly used for malaria treatment in this Hussein and El-Sebakhy, 1974;Rastrelli et al, 1997;Broussalis et al, 1999;Gadhi et al, 2001;Murillo et al, 2001;Wu et al, 2002;Hamill et al, 2000;Shi et al, 2004;Belay, 2011;Stangeland et al, 2011;Jimenez-Arellanes et al, 2012;Zamilpa et al, Tidjani et al, 1989;Stone, 1992;Hamill et al, 2000;Tabuti 2008;Ghimeray et al, 2009;Mbaya et al, 2010;Stangeland et al, 2011;Ashafa et al, 2012;Wang et al, 2013;Adia et al, 2014;Jamra et al, 2014;Mahilrajan et al, 2014;Prashanth and Krishnaiah, 2014;Yan et al, 2015;Kamatenesi et al, 2011;Anywar et al, 2016;Anand et al, 2016;Opio et al, 2017;Philip et al, 2017;Sinha et al, 2017 Bidens pilosa L. Geissberger and Séquin, 1991;…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto several animal and human studies have been done to study toxicity,[ 25 26 ] cell-mediated immunity,[ 27 ] and effectiveness of topical preparations[ 28 ] of M. citrifolia in its different forms. Similar animal and human investigations to study the antimicrobial efficacy,[ 29 30 ] toxicity,[ 31 32 33 ] and antisecretory property[ 29 34 35 ] of neem have been published in literature. Hence, this in vivo investigation to study the antimicrobial efficacy of herbal irrigants in an endodontic model was planned.…”
Section: Discussionmentioning
confidence: 98%